In situ Al2O3 incorporation enhances the efficiency of CuIn(S, Se)2 solar cells prepared from molecular-ink solutions. Issue 16 (15th April 2021) - Septina, Wilman; Muzzillo, Christopher P.; Perkins, Craig L.; Giovanelli, Anne Curtis; West, Thomas; Ohtaki, Kenta K.; Ishii, Hope A.; Bradley, John P.; Zhu, Kai; Gaillard, Nicolas
Abstract : In situ incorporation of nanosized amorphous Al2 O3 for defect passivation in solution-processed CuIn(S, Se)2 solar cells was demonstrated with significant efficiency enhancement. Abstract : We report an efficiency enhancement of solution-processed CuIn(S, Se)2 (CISSe) thin film solar cells via in situ incorporation of Al2 O3 . These films were produced using inks containing CuCl, InCl3, AlNO3 (Al/Al + In: 0.1) and thiourea dissolved in methanol. After spin coating of these solutions in air, samples were subjected to a selenization process. Auger electron spectroscopy depth-profiling analysis showed that Al is evenly distributed throughout the bulk of the film. Transmission electron microscopy revealed that AlNO3 precursor reacted with oxygen to form nanosized amorphous Al2 O3 grains located within the bulk and grain boundaries of CISSe, as well as at both the top and bottom interfaces. Power conversion efficiency (PCE) as high as 11.6% ( J SC : 35.8 mA cm −2, V OC : 518 mV, FF: 62.2%, no anti-reflection coating) was achieved with Al–CISSe solar cell devices integrated with CdS (chemical bath deposition, thickness: 80 nm) and ZnO/ITO bilayers (sputtered, thickness: 300 nm). The average PCE (10.1%, 〈 J SC 〉: 34.5 mA cm −2, 〈 V OC 〉: 491 mV, 〈FF〉: 59.8%) was nearly 4% (absolute) higher than that measured on CISSe baseline cells fabricated from solutions without Al (〈PCE〉 = 6.4%, 〈 J SC 〉: 32.8 mA cm −2, 〈 V OC 〉: 410 mV, 〈FF〉: 47.3%). This in situ Al2 O3 incorporation is speculated to play a role in the enhancement of the V OC and FF of the devices through passivation of defects in CISSe reducing interface and bulk recombination, as evidenced by a reduced defect density and an increased activation energy of the dominant recombination mechanism from capacitance and temperature-dependent V OC measurements, respectively.